The Hyperflexible Hip: Managing Hip Pain in the Dancer and Gymnast - Weber, Alexander E. (Sports Health, 2015)
CONTEXT: Dance, gymnastics, figure skating, and competitive cheerleading require a high degree of hip range of motion. Athletes who participate in these sports use their hips in a mechanically complex manner. EVIDENCE ACQUISITION: A search of the entire PubMed database (through December 2013) and additional searches of the reference lists of pertinent articles. STUDY DESIGN: Systematic review. LEVEL OF EVIDENCE: Level 3. RESULTS: Whether innate or acquired, dancers and gymnasts have some hypermobility that allows their hips to be placed in potentially impinging or unstable positions required for their given activity. Such extremes of motion can result in both intra-articular and extra-articular impingement as well as compensatory osseous and muscular pathology. In addition, dancers and gymnasts are susceptible to impingement-induced instability. Dancers with innate generalized hyperlaxity are at increased risk of injury because of their activities and may require longer recovery times to return to play. Both nonoperative and operative treatments (arthroscopic and open) have an important role in returning flexibility athletes to their preoperative levels of sport and dance. CONCLUSION: Because of the extreme hip motion required and the compensatory soft tissue laxity in dancers and gymnasts, these athletes may develop instability, impingement, or combinations of both. This frequently occurs in the setting of subtle pathoanatomy or in patients with normal bony anatomy. With appropriate surgical indications and the correct operative technique, the treating surgeon can anticipate high levels of return to play for the gymnast and dancer with hip pain.